Clinical Practice Guideline: Safe Medication Use in the ICU. Issue 9 (September 2017) - Kane-Gill, Sandra L.; Dasta, Joseph F.; Buckley, Mitchell S.; Devabhakthuni, Sandeep; Liu, Michael; Cohen, Henry; George, Elisabeth L.; Pohlman, Anne S.; Agarwal, Swati; Henneman, Elizabeth A.; Bejian, Sharon M.; Berenholtz, Sean M.; et al.
Abstract : Objective: To provide ICU clinicians with evidence-based guidance on safe medication use practices for the critically ill. Data Sources: PubMed, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, CINAHL, Scopus, and ISI Web of Science for relevant material to December 2015. Study Selection: Based on three key components: 1) environment and patients, 2) the medication use process, and 3) the patient safety surveillance system. The committee collectively developed Population, Intervention, Comparator, Outcome questions and quality of evidence statements pertaining to medication errors and adverse drug events addressing the key components. A total of 34 Population, Intervention, Comparator, Outcome questions, five quality of evidence statements, and one commentary on disclosure was developed. Data Extraction: Subcommittee members were assigned selected Population, Intervention, Comparator, Outcome questions or quality of evidence statements. Subcommittee members completed their Grading of Recommendations Assessment, Development, and Evaluation of the question with his/her quality of evidence assessment and proposed strength of recommendation, then the draft was reviewed by the relevant subcommittee. The subcommittee collectively reviewed the evidence profiles for each question they developed. After the draft was discussed and approved by the entire committee, then the document was circulated among all members for voting on the quality of evidence and strength of recommendation. Data Synthesis: The committee followed the principles of the Grading of Recommendations Assessment, Development, and Evaluation system to determine quality of evidence and strength of recommendations. Conclusions: This guideline evaluates the ICU environment as a risk for medication-related events and the environmental changes that are possible to improve safe medication use. Prevention strategies for medication-related events are reviewed by medication use process node (prescribing, distribution, administration, monitoring). Detailed considerations to an active surveillance system that includes reporting, identification, and evaluation are discussed. Also, highlighted is the need for future research for safe medication practices that is specific to critically ill patients. Abstract : Supplemental Digital Content is available in the text.